Sertifikasi Halal Industri pada Produksi Barang Gunaan Kemasan (Packaging) di PT. Indonesia Toppan Printing - Nuryakin, Rahmat Aji; Apriani, Triana; Setiadi, Setiadi; Solihin, Dadin; Athoillah, M. Anton (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
The research background examines the extent to which the domestic halal industrial ecosystem can dominate the domestic and global markets. Halal industrial estates must be able to support the needs for sources of raw materials and production that are halal certified, one of which is the Indonesian Packaging Company Toppan Printing. The aim of this research is to find out the elements and substances used in the manufacture of packaging used by PT. Indonesia Toppan Printing. This is done, among others, to realize the development of Halal Industrial Zones (KIH) in various regions of Indonesia, especially in West Java Province. This study uses descriptive qualitative research methods, data collection techniques through interviews, observation and documentation through the official website, scientific papers and literature. The data analysis technique uses descriptive analysis with the stages of data reduction, data presentation and conclusion. The results of this study can be concluded that the halal certification of plastic and paper packaging used for food, beverages, medicines, and toiletries (soap, toothpaste, shampoo, detergent, floor deodorizer, and clothes fragrance) produced by PT. ITP is part of the obligation for products that must be halal certified in accordance with Law Number 33 of 2014 concerning Guarantees for Halal Products, Government Regulation (PP) Number 31 of 2019 and Minister of Religion Regulation (PMA) Number 26 of 2019, as well as the latest regulations based on Law Number 39 of 2021, especially Article 14 where the clause states that